20‐Hydroxyecdysone‐upregulated proteases involved in Bombyx larval fat body destruction. Issue 6 (6th August 2018) - Guo, S.‐Y.; Wu, W.‐M.; Li, S.‐Y.; Liu, Y.; Ruan, Z. F.; Ye, M.‐Q.; Xiao, Y.; Zhong, Y.‐J.; Cao, Y.; Li, K.; Tian, L.
Abstract: During insect larval–pupal metamorphosis, the obsolete larval organs and tissues undergo histolysis and programmed cell death to recycle cellular materials. It has been demonstrated that some cathepsins are essential for histolysis in larval tissues, but the process of tissue destruction is not well documented. Fat body, the homologous organ to mammalian liver and adipose tissue, goes through a distinct destruction process during larval–pupal transition. Herein, we found that most of the Bombyx proteases – including Bombyx cathepsin B ( BmCatB ) (BmCatLL-2), Bombyx cathepsin D ( BmCatD ), Bombyx cathepsin L like‐1 (BmCatLL-1) and –2 (BmCatLL-2), Bombyx fibroinase ( BmBcp ), Bombyx matrix metalloprotease ( BmMmp ), Bombyx A disintegrin and metalloproteinase with thrombospondin motifs 1 ( BmAdamTS‐1 ), Bombyx A disintegrin and metalloproteinase with thrombospondin motifs like (BmAdamTS L) and Bombyx cysteine protease inhibitor (Bmbcpi)– were expressed highly in fat body during feeding and metamorphosis, with a peak occurring during the nonfeeding moulting or prepupal stage, as well as being responsive to 20‐hydroxyecdysone (20E). The aforementioned protease genes expression was upregulated by injection of 20E into the feeding larvae, while blocking 20E signalling transduction led to downregulation. Western blotting and immunofluorescent staining of BmCatB and BmBcp confirmed the coincident variation of their messenger RNA (mRNA) and protein level during the development and after the treatments. Moreover, BmCatB, BmBcp, BmMmp and BmAdamTS‐1 RNA interference all led to blockage of larval fat body destruction. Taken together, we conclude that 20E regulates larval fat body destruction by upregulating related protease gene expression and protein levels during larval–pupal transition.